Efficacy of Virtual Reality in Neurorehabilitation of Spinal Cord Injury Patients: A Systematic Review - Orsatti Sánchez, Bruno Alejandro; Diaz Hernandez, Octavio (Revista Mexicana de Ingenieria Biomedica, 2021)
<span style="color: #222222; font-family: 'Times New Roman', serif; font-size: small; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This systematic review (SR) analyzed the effectiveness of interventions using virtual reality (VR) technology as a neurorehabilitation therapy in people with spinal cord injury (SCI). The SR was developed under the guidelines of the PRISMA statement and the recommendations of the Cochrane Collaboration, along with the PEDro and National Institute of Health scales to assess the risk of bias and methodological quality. The Cochrane, IEEE, BVS/LILACS, MEDLINE/PubMed, and Web of Science databases were browsed to identify studies that, between 2010 and 2020, evaluated the efficacy of these therapies. Out of 353 retrieved studies, 11 were selected after applying the defined inclusion and exclusion criteria. These articles presented good methodological quality as they were mostly controlled clinical trials that analyzed mixed therapies with conventional therapies. Interventions based on non-immersive or immersive VR technology that achieved functional motor, balance, and psycho-emotional health improvement with positive effects on motivation, self-confidence, commitment, and active participation were identified in a total sample of 155 SCI patients. It was concluded that such VR technology is an effective tool of neurorehabilitation complementary to conventional therapies, which promotes functional improvement in SCI patients both in the clinic and at home.